Heterogeneous Firms and International Trade: The role of productivity and financial fragility - Tiziana Assenza; Domenico Delli Gatti; Jakob Grazzini; Giorgio Ricchiuti (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
In his seminal paper, starting from the premise that productivity is heterogeneous across firms, Melitz (2003) nicely accounts for the stylized fact that the level of individual productivity is key in determining the capability of a firm to export. In this paper we build a model along Melitz's lines to show that also financial capacity, captured by the level of individual net worth, affects the behaviour of firms on international markets. In our framework, in fact, the decision to export depends on both productivity and net worth, and both are heterogeneous across firms. We show that firms with low productivity may still be able to penetrate foreign markets provided they have enough net worth to incur the cost of exporting. However, even a really high net worth may not guarantee the presence in both domestic and foreign markets if the firm does not have a minimum level of productivity. Finally, we explore the effects of changes in transport costs, fixed costs for exporters and the financial constraints.
Keywords: E44; F12; F14; F21; 330; Productivity; Net Worth; International trade; Heterogeneous firms